UNDERPASS DALAM MANAJEMEN PEMBERITAAN MEDIA (Studi Deskriptif Kualitatif Tentang Manajemen Pemberitaan Kasus Underpass Makamhaji, Sukoharjo di Media Cetak Harian Umum Solopos dan Media Online Solopos.com Periode 1 Januari- 5 Maret 2013) - Nurjanah, Siti; Perwita, Alvika Hening; Herwindya, Sri (KOMUNITAS, 2013)
Solopos is the most existing press media in solo. Established in solo September 19thÂ  1997,inÂ  thatÂ  yearÂ  soloÂ  wasÂ  aÂ  cityÂ  thatÂ  hadÂ  aÂ  badÂ  reputationÂ  amongÂ  press communities..Â  RightÂ  nowÂ  SoloposÂ  wasÂ  expandingÂ  itsÂ  businessÂ  byÂ  creatingÂ  new media,it was online version of Solopos, Solopos.com. achievement that had been achieved by Solopos.com in the last 6 months (Januari-Juni 2013) was getting the most visitors in solo regional,about 50.000-60000 visitors a day. All of Solopos andÂ  Solopos.comÂ  successÂ  becauseÂ  ofÂ  supportedÂ  byÂ  goodÂ  newsÂ  management.Â  In orderÂ  toÂ  seeÂ  theÂ  differencesÂ  ofÂ  newsÂ  managementÂ  ofÂ  SoloposÂ  andÂ  Solopos.com, researcherÂ  connectedÂ  withÂ  reportingÂ  ofÂ  underpass,Â  planning,Â  organizing, actuating and controlling. The study was conductedÂ  in order to determine which news management applied in managing the news of Underpass. This research was a qualitative descriptive study. ResultsÂ  fromÂ  pressÂ  mediaÂ  managementÂ  researchÂ  inÂ  newsÂ  managementÂ  of UnderpassÂ  wasÂ  doneÂ  inÂ  fourÂ  stages,Â  planning,Â  organizing,Â  actuatingÂ  and controlling. In Planning Solopos.com was in the same side with Solopos butit was well planned because there was a planning meetingsÂ  or editorial meeting every day at 15.00, all things were discussed in the meeting, such as headline proposals, andÂ  theÂ  selectionÂ  of what theme wouldÂ  beÂ  written.Â  MeetingÂ  wasÂ  attendedÂ  byÂ  all mediacandidates. Organizing the management reports on print media and online mediaÂ  Solopos.comÂ  hadÂ  beenÂ  formedÂ  organizationalÂ  structureÂ  withitsÂ  positions and duties. Actuating in management reporting begunwith the reporting process, reportingÂ  wasÂ  doneÂ  byÂ  theÂ  sameÂ  reporter,Â  becauseÂ  theÂ  onlineÂ  mediaÂ  of Solopos.com didnât has it. This reporting was done by doing it right in the field, in MakamhajiÂ  Sukoharjo.Â  TheÂ  newsÂ  cameÂ  oberÂ  ofÂ  theÂ  rulesÂ  ofÂ  journalism. ControllingÂ  inÂ  managementÂ  reportÂ  wasÂ  doneÂ  byÂ  editorsÂ  thatÂ  thetheÂ  taskÂ  was overseeing directly in the field issues (editor Solopos), overseeing incoming and outgoingÂ  newsÂ  andÂ  watchingÂ  theÂ  newsÂ  toÂ  beÂ  published (Solopos.comÂ  editor)Â  as well as overseeing the content of the news reporterwith editing directly.